An Analysis of Image Processing Techniques and Tools in Medical Images - Chithra, S; Vijayabhanu, R (International Journal of Computer Sciences and Engineering, 2025)
Due to the great growth in the usage of computer technologies, image-processing techniques have become one among the most significant as well as rapidly used one in a broad variety of applications, particularly in medical imaging. Medical images are mostly used as radiographic techniques in disease recognition, clinical examinations along with treatment planning. The basic idea of medical image analysis is to develop imaging content. A typical medical imaging system is composed of five major processing phases i.e., image acquisition, pre-processing, segmentation, feature extraction/selection, and classification. Medical scan image usage machines are also constantly as fundamental. With these devices, it is possible to quicken and advance the errand of the examination of the diseases. Here, we have done a study on the present advanced techniques that have been used in various stages of medical image processing along with various medical image tools will be analyzed in a few directions. The essential focus of the assessment is to aggregate and examination on the medical apparatus in order to propose clients of different working systems on what sort of medical image devices to be utilized while investigating different kinds of imaging.